Design of less than 1 nm Scale Spaces on SnO2 Nanoparticles for High‐Performance Electrochemical CO2 Reduction. (23rd October 2021) - Kim, Mun Kyoung; Lee, Hojeong; Won, Jong Ho; Sim, Woohyeong; Kang, Shin Joon; Choi, Hansaem; Sharma, Monika; Oh, Hyung‐Suk; Ringe, Stefan; Kwon, Youngkook; Jeong, Hyung Mo
Abstract: Electrochemical carbon dioxide reduction reaction (CO2 RR) is a promising approach to mitigate CO2 concentration and generate carbon feedstock. Recently, the (sub‐)nanometer design of catalyst structures has been revealed as an efficient means to control the reaction process through the local reaction environment. Herein, the synthesis of a novel tin oxide (SnO x ) nanoparticle (NP) catalyst with highly controlled sub‐nanoscale interplanar gaps of widths <1 nm (SnO x NP‐s) is reported via the lithium electrochemical tuning (LiET) method. Transmission electron microscopy (TEM) and 3D‐tomo‐scanning TEM (STEM) analysis confirm the presence of a distinct segmentation pattern and the newly engineered interparticle confined space in the SnO x NP‐s. The catalyst exhibits a significant increase in CO2 RR versus hydrogen evolution selectivity by a factor of ≈5 with 20% higher formate selectivity relative to pristine SnO2 NPs at −1.2 VRHE . Density functional theory calculations and cation‐size‐dependent experiments indicate that this is attributable to a gap‐stabilization of the rate‐limiting *OCHO and *COOH intermediates, the formation of which is driven by the interfacial electric field. Moreover, the SnO x NP‐s exhibits stable performance during CO2 RR over 50 h. These results highlight the potential of controlled atomic spaces in directing electrochemical reaction selectivity and the design of highly optimized catalytic materials. Abstract : The space‐confinement approach to Sn‐based nanoparticles enhances the activity of Sn and its selectivity to formic acid. When the spacing between the active surfaces of Sn reaches <1 nm,  an order of magnitude increase in the current density and the product selectivity is observed for the electrochemical reduction of CO2 at a given applied potential.